2020
DOI: 10.1186/s43161-020-00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Level of awareness of dentists about the role of physiotherapy in temporomandibular disorders: a pilot study in Riyadh, Saudi Arabia

Abstract: Background Physiotherapy (PT) is a distinguished developing profession. It has a crucial role in treating temporomandibular disorders (TMD) as an effective intervention to reduce pain and improve TMD symptoms. Not all dentists are aware of the importance of collaboration with physiotherapists (PTs).Therefore, this study aimed to assess the level of dentists’ awareness about the role of PT in treating TMD, identify dentists’ willingness to collaborate with PTs, and create collaboration awareness. This cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In the present study, a majority were aware of the potential for PT to treat TMD, which is a more positive finding than in the study conducted by dentists in Saudia [46], where initially, only a small percentage referred patients to PT. Similarly, a study on dental practitioners in Karachi [45] reported a significant reluctance to refer patients.…”
Section: Discussionsupporting
confidence: 45%
“…In the present study, a majority were aware of the potential for PT to treat TMD, which is a more positive finding than in the study conducted by dentists in Saudia [46], where initially, only a small percentage referred patients to PT. Similarly, a study on dental practitioners in Karachi [45] reported a significant reluctance to refer patients.…”
Section: Discussionsupporting
confidence: 45%